Scrip.ting Media - Frank, Barnas; Barnas (newyork : Routledge Taylor and Francis Group., 2024)
bringing together p.rofessional standards p.ratices and jargon from across the industry scrip.ting media p.rovides a comp.lete overview of writing for divergent froms of media
index:p..187-191
Keywords: Scrip.ting Media